Optimism and pragmatism in mission cities: Exploring narratives for climate neutrality in Stockholm and Amsterdam - Chakravarty, Jasmine; Wickenberg, Björn ; 0000-0002-0838-9175; Mccormick, Kes ; 0000-0002-5093-160X (Energy Research & Social Science, 2026)
Climate neutrality of cities has emerged as a critical goal for sustainable urban development. This is typified by the mission in the European Union (EU) to achieve 100 climate neutral and smart cities by 2030. The idea of carbon or climate neutrality holds diverse interpretations. This paper investigates the dominant socio-technical imaginary for urban climate neutrality within the context of the EU Cities Mission, focusing on the cities of Stockholm and Amsterdam. Through narrative analysis of interviews and documents six key narratives are identified: 1) sustainable mobility and transport, 2) community engagement and just transition, 3) frontrunners in urban climate action, 4) the city as an experiment, 5) green economy and business innovation, and 6) the city as a complex system. This paper sheds light on the overlaps and contradictions between the narratives, suggesting opportunities for integrated policies centred on justice, leadership and experimentation. The analysis also reveals contrasting perspectives on the 2030 goal – namely an optimistic approach in the case of Stockholm and a pragmatic approach in the case of Amsterdam.
Keywords: Climate neutrality; Cities Mission; Missions; Socio-technical imaginaries; Narratives